Membrane Fouling Dynamics in the Clarification of Pomegranate Juice Using Egg Albumin Pretreatment: A Study on Hermia’s Empirical Models - Samreen,; , Ch V V Satyanarayana; , L Edukondalu; , Vimala Beera; , V Srinivasa Rao (Archives of Current Research International, 2025)
The present study investigated membrane fouling during the clarification of pomegranate juice after pretreatment with egg albumin. Pomegranate (Punica granatum L., Punicaceae) is a popular tropical non-citrus fruit known for its attractive aroma, refreshing flavor, and favorable Brix/acid ratio. This juice is commonly used in fruit-based beverages, either alone or mixed with other fruit juices. Pomegranates of the (cv. Ganesh) variety, sourced from the local market in Bapatla, Guntur District, Andhra Pradesh, were chosen for their high juice yield preferred by many juice processors and vendors. Hermia’s empirical models were applied to evaluate the fouling phenomena in microfiltration (MF) and ultrafiltration (UF) of pomegranate juice. The flux data was fitted into existing fouling models to elucidate the fouling mechanisms during membrane processing. The coefficient of determination (R²) values for the gel layer model ranged from 0.804 to 0.977 for the 0.2 µm pore size membrane when filtering pomegranate juice. These R² values suggest intermediate pore blocking followed by gel layer formation.